2013
DOI: 10.5888/pcd10.130124
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Matched Incentives to Encourage the Purchase of Fresh Fruits and Vegetables at Farmers Markets in Underserved Communities

Abstract: IntroductionFarmers market programs may increase access to more healthful foods and reduce the high prevalence of obesity in low-income communities. The objective of this study was to examine outcomes of the Fresh Fund farmers market program serving low-income neighborhoods in San Diego, California.MethodsThrough its Farmers Market Fresh Fund Incentive Program, the County of San Diego Health and Human Services Agency offered monetary incentives to government nutrition assistance recipients to purchase fresh pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 10 publications
2
73
0
Order By: Relevance
“…14,31,32 This study also had higher retention rates compared with several prior longitudinal incentive interventions, 30,3335 which may augment generalizability and help mitigate potential selection bias.…”
Section: Discussionmentioning
confidence: 85%
“…14,31,32 This study also had higher retention rates compared with several prior longitudinal incentive interventions, 30,3335 which may augment generalizability and help mitigate potential selection bias.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, studies evaluating financial incentive programs (e.g., coupons or vouchers), demonstrate at least modestly greater intent to purchase or consume—or reportedly increased purchasing or consumption—of fruits and vegetables among FM incentive recipients (Baronberg, Dunn, Nonas, Dannefer, & Sacks, 2013; Freedman, et al, 2011; Freedman, Choi, Hurley, Anadu, & Hebert, 2013; Jones & Bhatia, 2011; Kropf, Holben, Holcomb, & Anderson, 2007; Lindsay, et al, 2013; McCormack, Laska, Larson, & Story, 2010; Racine, et al, 2010; Webber, Balsam, & Oehlke, 1995; Weinstein, Galindo, Fried, Rucker, & Davis, 2014; Wheeler & Chapman-Novakofski, 2014; Young, et al, 2013). Other studies suggest that living near a FM is associated with greater produce intake (Gustafson, et al, 2013; Park, et al, 2011; Ruelas, et al, 2012) and that introducing FMs to communities may minimally increase reported consumption of select fruits and vegetables (Evans, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…38 In North Carolina, Jilcott Pitts et al (2015) in WIC. 39 Comparatively, a study in San Diego, California reported that 82% of a mostly Hispanic or Latino (49.5%) and Caucasian (18.0%) had never shopped at a FM (prior to intervention). 39 Collectively, these findings provide further evidence that the Healthy Roots For You pilot study must promote FM use by first considering cultural aspects of the target population, including communication channels and messages, sociodemographic factors and dietary habits.…”
Section: Discussionmentioning
confidence: 99%